1949
DOI: 10.1038/bjc.1949.11
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the Carcinogenic Properties of Urethane by Pentose Nucleotides

Abstract: URETHANE, which induces lung tumours in mice and rats (Nettleship and Henshaw, 1943; Jaffe, 1947; Cowen, 1947), also causes a notable decrease of malignant and normal leucocytes (Paterson, Haddow, ApThomas and Watkinson, 1946; Cowen, 1947). The present study was undertaken to investigate any correlation between the carcinogenic and leucopaenic properties of urethane.The mixture of pentose nucleotides as prepared from yeast nucleic acids is used clinically in the treatment of agranulocytosis, and it has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1952
1952
1969
1969

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Recent experiments have discounted the assumption that urethane has a direct nucleotoxic action in initiating tumors (5,6,12). Evidence perhaps in favor of an influence upon nucleic acids, however, has been reported by Cowen (13). Since the effect of pentosenucleotides on leucocytes is the opposite of that of urethane, he tested the protective effect of these substances upon its carcinogenic action.…”
mentioning
confidence: 99%
“…Recent experiments have discounted the assumption that urethane has a direct nucleotoxic action in initiating tumors (5,6,12). Evidence perhaps in favor of an influence upon nucleic acids, however, has been reported by Cowen (13). Since the effect of pentosenucleotides on leucocytes is the opposite of that of urethane, he tested the protective effect of these substances upon its carcinogenic action.…”
mentioning
confidence: 99%
“…(8) tested the activity of a series of esters of carbamic acid, alkylated urethanes, and miscellaneous compounds for oncogenic activity and found them all inactive or not nearly as active as the parent substance, urethane. Cowen (25), using a small series of mice, reported that pentose nucteotides inhibited the carcinogenic properties of urethane. We have tested a few substances chemically related to urethane for activity against PVM.…”
Section: Effect Of Urethane Onmentioning
confidence: 99%
“…This carbamate also inhibits the antibacterial action of low levels of sulfonamides (Johnson et al, 1943) and causes a decrease in the catalase content of Escherichia coli (Pontieri, 1953). The antagonism of the leucopenic and carcinogenic properties of urethan by pentose nucleotides (Cowen, 1949) and the reversal of urethan inhibition of E. coli by 2,6-diaminopurine (Skipper and Schnabel, 1952) suggest an interference with nucleic acid metabolism.…”
mentioning
confidence: 99%